Impacts of the pandemic on current age's schooling and the significance of advanced change of day to day existence - SRINIVAS, Dr. KUMMARI; REDDY, MANCHIREDDY CHANDRA SEKHAR; RAO KODALI, DHANUNJAYA; PASHA, MOHAMAD JAHANGIR (The journal of contemporary issues in business and government, 2019)
Digital technology has been a constant presence in the lives of today's children since they were born. There are still a number of digital divisions in society that have an impact on today's youth and their ability to prepare for a technologically advanced future. For the sake of today's young and their technologically dependent future, educational institutions must undergo massive digital change. In light of the COVID-19 epidemic, schools and education have had to undergo a drastic transformation in their policies. The influence of the COVID-19 pandemic on basic education, the diversity of digital divides that have formed and reinforced, and the likely difficulties that have been documented are all part of this study. Research in information management should pay more attention to children, their digitalized life, and their fundamental education. We should take into account this generation's demands when it comes to the education we give in the framework of higher education, but we should also seek to impact their basic education in the hopes of nurturing their interest in this sector and potentially making it a career choice for them.